Recommendations for diagnosis and treatment of Atypical Hemolytic Uremic Syndrome (aHUS): an expert consensus statement from the Rare Diseases Committee of the Brazilian Society of Nephrology (COMDORA-SBN) - Vaisbich, Maria Helena; Andrade, Luis Gustavo Modelli de [UNESP]; Barbosa, Maria Izabel Neves de Holanda; Castro, Maria Cristina Ribeiro de; Miranda, Silvana Maria Carvalho; Poli-de-Figueiredo, Carlos Eduardo; Araujo, Stanley de Almeida; Ernandes Neto, Miguel; Penido, Maria Goretti Moreira Guimarães; Sobral, Roberta Mendes Lima; Ferra Neto, Oreste; Neves, Precil Diego Miranda de Menezes; et al. (FapUNIFESP (SciELO), 2025)
Atypical hemolytic uremic syndrome (aHUS) is a rare cause of thrombotic microangiopathy (TMA) caused by the dysregulation of the alternative complement pathway. The diagnosis of TMA is made clinically by the triad: microangiopathic hemolytic anemia, thrombocytopenia, and organ damage (mainly acute kidney injury). The heterogeneity of clinical manifestation and the lack of a gold standard diagnostic test makes the precise diagnosis of aHUS a challenging process that may impact patient management. Until one decade ago, there was no specific treatment for aHUS and patients were submitted to plasma therapy (plasma exchange and/or plasma infusion) and/or liver transplantation, procedures that are not free of serious complications and that do not address the underlying pathophysiology of the disease. Since 2011, an anti-C5 complement monoclonal antibody has been approved by the Food and Drug Administration (FDA) for aHUS patients beginning a new era in treatment. Clinical trials on new complement inhibitors may also add to the treatment portfolio in the future. The Brazilian population is a mixed race with a unique genetic and clinical profile. This consensus aims to offer recommendations for the diagnosis and treatment of patients with aHUS in this population based on expert experience, data from the aHUS Brazilian Registry and literature review. The GRADE system was used to classify the quality of the evidence.